Use and value of systematic reviews in English local authority public health: a qualitative study - Emily South; Theo Lorenc (BMC, 2020)
Abstract Background Responsibility for public health in England transferred from the National Health Service to local authorities in 2013, representing a different decision-making environment. Systematic reviews are considered the gold standard of evidence for clinical decision-making but little is known about their use in local government public health. This study aimed to explore the extent to which public health decision-makers in local authorities engage with systematic reviews and how they do so. Methods Semi-structured interviews were conducted with senior public health practitioners (n = 14) in Yorkshire and the Humber local authorities. Sampling was purposive and involved contacting Directors of Public Health directly and snowballing through key contacts. Face-to-face or telephone interviews were digitally recorded, transcribed verbatim and analysed using the Framework Method. Results Public health practitioners described using systematic reviews directly in decision-making and engaging with them more widely in a range of ways, often through a personal commitment to professional development. They saw themselves as having a role to advocate for the use of rigorous evidence, including systematic reviews, in the wider local authority. Systematic reviews were highly valued in principle and public health practitioners had relevant skills to find and appraise them. However, the extent of use varied by individual and local authority and was limited by the complexity of decision-making and various barriers. Barriers included that there were a limited number of systematic reviews available on certain public health topics, such as the wider determinants of health, and that the narrow focus of reviews was not reflective of complex public health decisions facing local authorities. Reviews were used alongside a range of other evidence types, including grey literature. The source of evidence was often considered an indicator of quality, with specific organisations, such as Public Health England, NICE and Cochrane, particularly trusted. Conclusions Research use varies and should be considered within the specific decision-making and political context. There is a need for systematic reviews to be more reflective of the decisions facing local authority public health teams.